2018
DOI: 10.46743/2160-3715/2018.3508
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Perspective of Wellbeing: A Qualitative Study

Abstract: Cross-cultural research suggests that wellbeing may be experienced differently by distinct populations. While research on wellbeing in non-Western populations has increased, there is limited empirical evidence regarding wellbeing in Indonesia. As the fourth largest country in the world, and with its unique socio-cultural characteristics, the potentially distinctive Indonesian experience of wellbeing has been overlooked by international scholars. The present research investigated the Indonesian perception of we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…Several previous studies have shown that the main source of happiness and satisfaction in Indonesian society is family . Their well-being will increase if they can provide benefits to the family (Maulana et al, 2018). Therefore, further research is warranted to investigate parental well-being in the context of Indonesian culture.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies have shown that the main source of happiness and satisfaction in Indonesian society is family . Their well-being will increase if they can provide benefits to the family (Maulana et al, 2018). Therefore, further research is warranted to investigate parental well-being in the context of Indonesian culture.…”
Section: Resultsmentioning
confidence: 99%
“…Pflug [38] suggests this was due to the history of material scarcity particularly among black South Africans. Similarly, in a study by Maulana et al [40] on Indonesian adults, the researchers found that the concept of happiness was equated to a state of "satisfaction" across 3 domains: basic needs (e.g. food, shelter and financial independence); social needs (e.g.…”
Section: If You Are Over-ambitious You Are Never Happy With What You ...mentioning
confidence: 93%
“…Figure 3 outlines the various theoretical justifications for the studies, with 'general wellbeing' being the most common justification (defined as those studies which refer to the value of applying wellbeing measures more generally), utilised in 34% of studies (e.g. Maulana, Obst, & Khawaja, 2018). Studies could be classified under more than one theoretical justification.…”
Section: Study Selectionmentioning
confidence: 99%